The Mathematical Modeling for the Work of Electrochemical Sensors and Biosensors, Based On Conducting Polymers, In The Process Of the Common Detection of Two Sulfonic Acids - Романів, Людмила Вікторівна (Applied Journal of Environmental Engineering Science, 2017)
The mathematical model for the potentiostatic work of CP-based electrochemical sensors and biosensors, used for the detection of two strong organic acids with the common “acid” functional group (using the example of –SO3H group), was developed and analyzed by the using of linear stability theory and bifurcation analysis. The steady-state stability conditions, corresponding to the better response, were developed. The presence of oscillatory and monotonic instabilities was also confirmed.
Keywords: food safety, intoxication prevention, sulphoacid, conducting polymer, electrochemical sensors, electrochemical oscillations, steady-states’ stability.